The Influence of Self-Efficacy on Academic Procrastination among STAI Balikpapan Students - Aufa Hanifan Hadi; Iskandar Yusuf (Feelings: Journal of Counseling and Psychology, 2025)
A student is someone who is studying at a university, for example polytechnics, institutes, colleges, universities and others. This is in accordance with Law No. 12 of 2012 concerning general provisions which explain that students are students at the Higher Education level. Students have duties and responsibilities in higher education, namely academics, in this case studying, doing assignments, presentations, group work and so on. In accordance with Law No. 12 of 2012 concerning the implementation of higher education, article 7 paragraph 3 point h explains that the implementation of other tasks is to ensure the development and achievement of higher education goals. Based on the results of interviews conducted by researchers, it is hoped that students should prioritize academics more than non-academic activities. Lecturers also hope that students are punctual in submitting assignments, attend class if the course is face-to-face, and do not copy friends' assignments.